Letter to Jane Tolmach from Thomas E. Rees - Thomas E. Rees:::::: (1966)
A letter from Congressman Thomas M. Rees to Jane Tolmach, congratulating her on her new role as Women's Chairman for Southern California of the State Central Committee.